The New Lex Mercatoria: Applicability of Lex Mercatoria as Substantive Law in International Commercial Arbitration - Mwangi, Maitho Edwin (Department of Commercial Law, 2014)
The study addresses the controversy surrounding the existence and validity of the lex mercatoria as an autonomous legal system. The overall objective of the study is to evaluate whether the lex mercatoria has attained the status of an autonomous system of law. Traces of the law merchant derive from the early ages, a time when merchants began to traverse the world in search for new markets. This created a need to govern their businesses and conduct to avoid the interference of their affairs by sovereign authorities. The rules formulated by the merchants were codified into the laws of states giving rise to the oblivion of the law merchant. There has arisen over time a debate on the existence of a new lex mercatoria. The study evaluates the existence and viability of the new lex mercatoria by answering the following pertinent research questions: what are the sources of the new lex mercatoria; are the criticisms levelled against the lex mercatoria viable; has the lex mercatoria attained the status of an autonomous legal system and if not, what are the reasons behind its rejection? This study is limited to international commercial arbitration since it is through arbitration that the applicability of lex mercatoria as substantive law has been made possible. Recognition of state-less awards, the modernization of arbitration laws by African states, recognition by the European Union of the possibility of application of general principles of law reflect trends towards the acceptance of the autonomous nature of lex mercatoria.